Combinatorial Studies into the Effect of Thermally Inter-Diffused Magnesium on the Kinetics of Organic Coating Cathodic Delamination from Zinc Galvanized Steel - Natalie Wint (Journal of The Electrochemical Society, 2020)
This paper describes a high-throughput study into the role of Mg in preventing corrosion driven coating disbondment of organic coatings from Zn-Mg alloy galvanized steel. A graded Mg wedge is applied to a hot-dip zinc galvanised steel substrate using physical vapour deposition, and subsequently annealed to produce metallic inter-diffusion and formation of Mg2Zn11 intermetallic. An overcoat of electrically insulating polyvinyl butyral (PVB) is applied and corrosion is initiated from a penetrative coating defect using an aqueous electrolyte. The variation in Mg coating weight across the wedge facilitates a systematic investigation of the effect of Mg on Volta potential and the rate of corrosion driven cathodic coating disbondment using scanning Kelvin probe (SKP) potentiometry. The rate of cathodic disbondment is shown to decrease rapidly even at very low Mg coating weight (corresponding to 25 nm thickness before annealing). The results are explained in terms of the galvanic polarity of the corrosion cell formed between Zn exposed at the defect site, and the intact Zn-Mg layer at the metal-organic coating interface.